Knowledge management in the construction of peace in territories made up of Groups of Special Constitutional Attention in Colombia (Encuentros, 2024)
The article focuses on a theoretical reflection on Knowledge Management in the construction of peace from a Human Rights perspective in Constitutional Attention Groups in Colombia. The relationship and dynamic interaction of the Knowledge Management, peace and Constitutional Care Groups categories is proposed through the redefinition of social processes and interactions from the conception of territory. Among the results, it was possible to show that Knowledge Management becomes a powerful process for the recognition of community knowledge, dialogue with different cosmologies and the generation of new knowledge with the possibility of incidence and social transformation.
Keywords: Knowledge Management; Peace building territory; Human rights; Groups of special constitutional attention